Trygg i stadslandskapet? - Larson, Anna Maria (2008)
In this thesis, theories regarding gender and spatial planning are applied to the comprehensive plan Fortuna och Hemgården in eastern Malmö. Independent of factors like class, ethnicity and age women experience lack of safety to a larger extent than men do.